Including Institutions : Boosting Resilience in Europe - World Bank (World Bank, Washington, DC, 2020)
The 2008 crisis marked the beginning of a lost decade for many countries - and many people - in the European Union (EU). The crises of 2008 and 2012 halted, and in some countries undid, a decade of growth and economic convergence across the EU. This report argues that the economic shocks revealed large differences in the resilience of individual economies, associated with differences in the quality of country-level institutions that shaped the absorption and response to these shocks. The report is in two parts. Part one uses an inclusive growth framework that assesses the trends in economic growth, the sharing of that growth, and its resilience. Part two looks closer at a key aspect of resilience: what are the key institutions that affect an economy’s resilience or capacity to respond to shocks. This report finds that in many European countries, growth was shared with low-income households; but these households were shielded less well during downturns. During the crises, the poorest fifth of households in both Central Europe and Southern Europe saw deeper drops in incomes and for longer periods than the median household. The report puts a special emphasis on a country’s membership of the European Monetary Union (EMU) - the eurozone. The report finds that resilience of inclusive growth varied across EU countries, when faced with the global financial crisis of 2008 and the euro crisis of 2012, because of the quality of institutions. This report finds that boosting resilience of EU member states should start with improving the real exchange rate institutions. Resilience and flexible and coordinated real exchange rate adjustments are short-term measures to cushion shocks and support adjustment.